(untitled) (Medico Legal Update, 2020)
Human Development, including education and health, is one of the three pillars that are indicators in the development concept of Sustainabale Development Goals (SDGs). State nutrition status of Indonesia from year to year shows improvements although still faced with various challenges that are quite severe. The purpose of this research is to analyze the influence of individual characteristics (age, gender and education) on the performance of nutrition Program in the Community Health center of Ambon. This type of research is quantitative research with the design of Cross Sectional Study. The population in this study is all the energy Center public Health that works in 22 public health centres as much as 54 people. Sampling techniques in a total sampling way. The results showed that there were no age and gender relations with the performance of the nutrition Program in the Community Health center of Ambon with the value P = 0138 and 0519. However, there is an education relationship with the implementation of nutrition Program in the Public health center of Ambon City with the value P = 0.004. Therefore, the Public health center can apply for a nutritional officer to get a scholarship or provide facilities and to resupply the nutritional officers to pursue higher education in order to make nutrition performance more maximal.